The Role of Relief Seed and Voucher Programme in Inputs Market Development - Walt, Wynand J. van der (FANRPAN, 2006)
Distribution of relief seed following natural disaster has become a common phenomenon in the SADC region, and many member states have had government, donor and NGO support in place for decades.